Mudarabah vs Musharakah: Which Profit Loss Sharing Scheme Poses Greater Financing Risk? - Pramudita, Tita Hesti; Aji Purba Trapsila (Universitas Airlangga, 2025)
Existing literature generally only discusses the impact of Profit and Loss Sharing (PLS)-based financing in general on the financing risk of Islamic banks. This study conducts a more in-depth analysis by separating PLS into two main schemes, namely Mudarabah and Musharakah, to explore the differences in risk levels between the two. The data used comes from the annual reports of 7 Islamic Commercial Banks in Indonesia during the 2019-2023 period, which were analyzed using panel data regression methods. The results show that Mudarabah financing is not riskier than Musharakah. Specifically, Mudarabah financing has no significant effect on financing risk, while Musharakah financing shows a positive and significant effect on increasing financing risk. These findings have important implications for Islamic bank risk management in allocating financing based on the PLS scheme.